Community Based Planned Intervention Targeting Perceptions, Attitudes and Health Seeking Behaviour Regarding Cancers in New Delhi: The Study Protocol - Tulika Seth; Atul Kotwal; Rakesh Thakur; GK Rath; DN Sharma; Jitendra Nagpal (National Journal of Community Medicine, 2019)
Background: In view of the increasing burden of cancers in devel- oping countries and this study was conducted to first understand community needs and perceptions, secondly to design and im- plement evidence based preventive strategies, and lastly to test the short-term outcome of these strategies in the field.